Application of botulinum toxin in maxillofacial field: Part II. Wrinkle, intraoral ulcer, and cranio-maxillofacial pain - Kyung-Hwan Kwon; Kyung Su Shin; Sung Hee Yeon; Dae Gun Kwon (SpringerOpen, 2019)
Abstract Botulinum toxin (BTX) is used in various ways such as temporarily resolving muscular problems in musculoskeletal temporomandibular disorders, inducing a decrease in bruxism through a change in muscular patterns in a patient's bruxism, and solving problems in patients with tension headache. And also, BTX is widely used in cosmetic applications for the treatment of facial wrinkles after local injection, but conditions such as temporomandibular joint disorders, headache, and neuropathic facial pain could be treated with this drug. In this report, we will discuss the clinical use of BTX for facial wrinkle, intraoral ulcer, and cranio-maxillofacial pain with previous studies and share our case.